Female Leaders' Experiences in Azerbaijan's Public Schools Within Early Career Experience - Gurbanbayli, Zabita; Musazada, Khayala; Suleymanli̇ Jafarova, Fatima; Orujaliyeva, Narmin (ADA University, 2024)
This study explored the early career experiences of female leaders in Azerbaijani public schools, emphasizing their points of view in both urban and rural environments. The following research questions guided the study: 1. What are the female leaders' early career experiences in the context of Azerbaijan public schools? a.What factors contribute to the differences in the female leaders' early career experiences in urban and rural areas of Azerbaijan public schools? This exploratory qualitative study focused on the viewpoints of female school principals in both urban and rural settings as it explores their early career experiences in Azerbaijani public schools. Even though more women are assuming leadership positions in Azerbaijani public schools, these female leaders still encounter many obstacles that limit their ability to develop effectively, especially at the beginning of their careers. This research emphasizes the cultural, socioeconomic, and gender-related aspects that influence these issues, building on the findings of Oyneniran and Lili (2020). It also looks at the different experiences of female leaders in rural and urban areas, pointing out that rural leaders frequently handle a wider range of duties with fewer resources (Wirth, 2001). Six participants, three from rural and three from urban areas, participated in semi-structured interviews for the study's comprehensive review of these experiences. The research attempted to provide insights that might help the success and professional growth of female leaders in Azerbaijan's public education sector by identifying the variables causing these discrepancies.
Keywords: Women in education -- Azerbaijan; Leadership in education -- Azerbaijan; Female school principals -- Azerbaijan -- Career development; Rural schools -- Leadership -- Azerbaijan; Education